Growth and Immune Response of Pond-Reared Giant Freshwater Prawn Macrobrachium osenbergii Post Larvae Fed Diets Containing Chlorella vulgaris - Maliwat, Gian Carlo F (Archīum Ateneo, 2020)
A 70-day feeding trial was conducted to evaluate the efficacy of Chlorella vulgaris supplementation in diets of giant freshwater prawn (Macrobrachium rosenbergii) post larvae. Resistance of the prawns against Aeromonas hydrophila and several immune parameters (total hemocyte count and prophenoloxidase activity) were also assessed in the study. Iso-nitrogenous, iso-lipidic, and iso-caloric prawn feeds were prepared utilizing a fishmeal based positive control diet (F0) and four dietary treatments with C. vulgaris inclusion levels of 2 (F2), 4 (F4), 6 (F6), and 8 (F8) %. Post larvae of M. rosenbergii were stocked randomly (mean initial body weight of 0.39 ± 0.38 g) in fifteen net cages (8.1 m × 8.9 m with an average depth of 1 m) in an earthen pond for the assessment of growth parameters. Overall growth indices for prawn fed Chlorella containing diets were enhanced in comparison to the control treatment. Prawn fed diets with Chlorella showed significantly higher (P < 0.05) prophenol oxidase activity, total hemocyte counts, and survival rates post bacterial infection. These findings demonstrated that inclusion of 4%, 6%, and 8% C. vulgaris in prawn diets provided optimal growth rates and improved immunity of the post larvae.